2018
DOI: 10.1155/2018/8947230
|View full text |Cite
|
Sign up to set email alerts
|

CD11c-Specific Deletion Reveals CREB as a Critical Regulator of DC Function during the Germinal Center Response

Abstract: Dendritic cells (DCs) are crucial for the balance between immune response and tolerance, but the molecular mechanism regulating development, differentiation, and homeostasis are poorly understood. The transcriptional activator CREB is involved in regulating different cells of the innate and adaptive immune system and is a transcriptional regulator of development, survival, activation, or proliferation in macrophages, dendritic cells, B cells, and T cells. To directly examine the role of CREB in the regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…CREB is thought to mediate interleukin 10 (IL-10) expression by macrophages (Ananieva et al, 2008) and DCs (Alvarez et al, 2009). Specific knockout of CREB in DCs leads to an impairment in immune processes related to DC function, specifically the expression of B cell lymphocytes in germinal centers (Ohl et al, 2018).…”
Section: Creb In Pbmcmentioning
confidence: 99%
“…CREB is thought to mediate interleukin 10 (IL-10) expression by macrophages (Ananieva et al, 2008) and DCs (Alvarez et al, 2009). Specific knockout of CREB in DCs leads to an impairment in immune processes related to DC function, specifically the expression of B cell lymphocytes in germinal centers (Ohl et al, 2018).…”
Section: Creb In Pbmcmentioning
confidence: 99%
“…S1 and Materials and Methods). We chose the CD11c Cre to silence ICAM-1 expression, since it has been extensively used for targeting various genes in different DCs ( 3537 ). The major DC subset involved in CD8 priming, namely cDC1, lost the majority of their ICAM-1 in CD11c-Cre:ICAM-1 fl/fl mice in both resting as well as skin vaccinated popliteal (skin-draining) LNs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ICAM-1 on subcapsular macrophages may also modulate the efficiency of viral antigen spread inside infected LNs ( 32, 33 ), and B cell expressed ICAM-1 ( 34 ) may contribute to CD4 T cell differentiation. We have therefore constructed a new strain of ICAM-1 fl/fl mice and generated DC ICAM-1 knockout mice by crossing the ICAM-1 fl/fl strain with mice expressing the Cre recombinase under the DC enriched CD11c promoter ( 3537 ). We used these mice to follow the specific contributions of DC ICAM-1 to CD8 priming and differentiation into effector and memory CD8 T cells in distinct vaccinated and virus-infected LNs ( 38, 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…CD11c is also a marker of dendritic cells. It has been reported that CD11c-positive dendritic cells promote the formation of germinal centers in the steady state and their response after immunization [63]. Furthermore, it has been suggested that, in follicular lymphoma, the presence of CD11c-positive dendritic cells in the tumor micro-environment is involved in tumor progression or recurrence by supporting regulatory T-cell infiltration [64].…”
Section: Discussionmentioning
confidence: 99%